Memory Culture in Scandinavian Studies: Abstract Book and Program of the 33d Study Conference of the International Association for Scandinavian Studies (IASS), Vilnius, August 3-6, 2021 - Steponavičiūtė Aleksiejūnienė, Ieva; Vaicekauskienė, Loreta; Zukienė, Rūta (Vilnius University Proceedings, 2021)
The history of IASS goes back to Cambridge 1956 and counts 32 study conferences. The latest five of these were hosted by the Universities of Lund (Sweden, 2010), Riga and Daugavpils (Latvia, 2012), the University of Agder in Kristiansand (Norway, 2014), the Universities of Groningen (The Netherlands, 2016) and Copenhagen (Denmark, 2018). The Centre of Scandinavian Studies at Vilnius University was proud of being entrusted with hosting the 33rd conference of IASS and we were thrilled to anticipate everyone coming to Vilnius in summer 2020. However, it became the first time when the conference would basically be held on the World Wide Web − as the world was hit by a global disaster – the Covid19 pandemic. For the same reason, and again for the first time in the history of IASS, the conference was put on hold and from now on it will probably always be held in odd years, the next conference being already scheduled for 2023. However, despite the fact that the conference of 2021, due to these reasons, was somewhat unusual in its format it was lacking neither in academic quality, nor in the joy of interaction with old and new colleagues that IASS conferences have always been famous and popular for.
Keywords: Memory Culture; Vilnius University; IASS conference; Scandinavian Studies